Culex quinquefasciatus Mosquitoes Resist Acquisition of Methicillin-Resistant Staphylococcus aureus: Insights from Field and Laboratory Studies - Waseema Arif; Gowdham Thangaraj; Pushpa Srinivasan; Srikanth Srirama; Panneer Devaraju (MDPI AG, 2024)
The emergence of antimicrobial resistance (AMR) in pathogens and their spillover into the environment have become a global public health menace. Insects can acquire these pathogens from the environment and would serve as mechanical and biological vectors. The current study assessed the ability of Culex quinquefasciatus mosquitoes to acquire methicillin-resistant Staphylococcus aureus (MRSA) through the exposure of the mosquitoes to the pathogen via rearing water, blood feed, or a feeding membrane under laboratory conditions. In addition, mosquito immatures collected from their habitat in the vicinity of hospitals, veterinary dispensaries, and butcher shops at 15 study sites in Puducherry were screened for MRSA infection. All samples were subjected to the culture-based isolation of S. aureus from the surface and homogenate. The presence of the S. aureus-specific nuc gene and the genes that confer resistance to methicillin (mecA and mecC) were screened using PCR tests. MRSA was not evident either on the external surface or in the homogenate of the mosquitoes emerging from the larvae reared in the MRSA-spiked water or those fed with MRSA through blood or smeared membranes. Furthermore, the presence of MRSA was not evident in any of the field-caught mosquitoes. Hence, we conclude that C. quinquefasciatus mosquitoes are impervious to MRSA colonization.